A STUDY ON STATUS OF CLIENT SATISFACTION IN PATIENTS ATTENDING GOVERNMENT HEALTH FACILITIES IN AGRA DISTRICT - Anand, D; Kaushal, S K; Gupta, S C (Indian Journal of Community Health, 2012)
Background: It is easier to evaluate the patient’s satisfaction towards the service than evaluate the quality of medical services that they receive. Patient satisfaction indicators remain stable over time as oppose to clinical indicators which will be changed with technology and pace of medical progress. Objectives: 1) To assess the level of satisfaction of patients attending government health facilities.2) To identify the area of low satisfaction at Government health facility. Methodology: Multistage sampling technique was used for selecting primary and secondary level health facilities. Patients were interviewed, when they were leaving health facility by using pretested, predesigned, semi-structured schedule. Results: A total of 600 clients were interviewed in this study and it was found that there was high level of satisfaction with signboard/display, courtesy and respect given by doctor, overall time duration given by doctor, skills of doctor, effectiveness of health services in solving problem, cost incurred on health services, and behavior of paramedical staff. Whereas comparatively low level of satisfaction was found regarding timings of OPD, registration procedure, waiting time, Cleanliness and comfort of waiting area and examination room, privacy measures and behavior of other non medical staff member.Major causes of dissatisfaction at primary level were Comfort and cleanliness of waiting area and service area, privacy measures, overall time duration given by doctor and behavior of supporting staff. However at higher i.e. secondary and tertiary level major causes found were inadequate OPD timing, mismanaged registration procedure and long waiting time to seek doctor. Conclusion: To raise level of patients satisfaction there should be capacity building,training and orientation programmes for health professonals.